A Quasi-Experimental Study Investigating the Impact of a Lifestyle Redesign Program on the Well-Being of Korean University Students - Sun-Joung Leigh An; Gyu-Rin Kim (Hindawi-Wiley, 2024)
Background. Korean university students (KUS) face numerous challenges that can jeopardize their well-being, including academic stress, peer pressure, irregular sleep patterns, unhealthy eating habits, lack of physical exercise, and difficulties in time management, resulting in unhealthy habits and fluctuations in lifestyle. Consequently, there is a growing need for interventions tailored to this population. Aim. This study explored the effects of a Lifestyle Redesign (LR) intervention on Korean university students' well-being including occupational participation, satisfaction, perceived stress levels, and quality of life. Method. A quasi-experimental study with 33 KUS (17 intervention, 16 control) assessed the effects of a 10-week LR intervention on well-being of the students. Pre- and postintervention changes were measured using Canadian Occupational Performance Measure (COPM), Stress Response Inventory (SRI), and World Health Organization Quality of Life Scale Abbreviated Version (WHOQOL-BREF). The intervention, delivered by trained OTs, comprised of individual and group sessions. Results. Statistically significant improvement was observed in occupational performance. While statistical significance was not consistently achieved in the rest of other areas, the LR group displayed positive trends. The LR group exhibited higher COPM satisfaction scores, lower SRI scores (indicating reduced stress), and elevated WHOQOL-BREF scores compared to the control group. Conclusion. This study contributes to the understanding of the importance of addressing lifestyle changes and habits in the well-being of university students, especially in the context of academic stress and peer pressure. Future research with larger, more diverse samples and extended intervention periods may offer further insights into the benefits of LR programs in university settings.